Effect of potent nucleos(t)ide analog on alpha fetoprotein changes and occurrence of hepatocellular carcinoma in patients with chronic hepatitis B - Qianqian Ma; Junzhao Ye; Ling Luo; Yanhong Sun; Wei Wang; Shiting Feng; Bing Liao; Bihui Zhong (Infectious Agents and Cancer)
Abstract Background Successful antiviral therapy significantly decreases the incidence of hepatocellular carcinoma (HCC) in patients with chronic hepatitis B (CHB). Alpha-fetoprotein (AFP) in the serum is a valuable early indicator of HCC. However, it is unclear whether different antiviral medications have varying effects on AFP levels. The purpose of this study was to evaluate this issue in those treated with entecavir (ETV) versus tenofovir disoproxil fumarate (TDF). Methods We prospectively enrolled treatment-naive CHB adults who commenced treatment with ETV or TDF. Their changes in biochemical, virological, and fibrosis parameters and the elevation of AFP or development of HCC during follow-up were analyzed. Results A total of 1942 CHB patients were included (10–90% follow-up time 3–60 months), and 104 patients with elevated AFP (5.3%) and 27 patients with HCC development (1.4%) were identified during the follow-up. The difference in the cumulative incidence of AFP abnormalities and HCC was statistically significant between patients who received ETV or TDF therapy. Multivariate Cox regression showed that elevated liver stiffness with shear wave elastography (Hazard ratio (HR) = 1.05, 95% Confidence interval (CI) 1.03–1.08, P < 0.001) and abnormal AFP at baseline (HR = 1.00, 95% CI 1.00–1.00, P < 0.001) were independent risk factors for abnormal AFP in CHB patients, while shear wave elastography (HR = 1.07, 95% CI 1.02–1.12, P < 0.001) was also independent risk factor for HCC. Similar results were obtained after propensity score matching (PSM) analysis. The combination of shear wave elastography (SWE), mPage-B score, age and type 2 diabetes mellitus had an area under the curve of 0.838 (P < 0.001) in predicting the occurrence of HCC. Conclusions Similar AFP elevation and HCC development rates were observed in CHB patients treated with ETV or TDF. Elevated SWE and abnormal AFP at baseline were independent risk factors for abnormal AFP in CHB patients.